Airbnb and the paradox of the body: The biopolitical management of hosts in four tourist towns in New Zealand. - Pennell S (SAGE Publications)
irbnb is emblematic of a set of business practices commonly known as ‘the sharing economy’. It is a disruptive business model of homestay accommodation that has exploited conditions of growing precarity of work since 2008. Work precarity is particularly evident in regional tourist areas in New Zealand, which historically experience seasonal, part-time work and low wages. Airbnb draws specifically on the rhetoric of micro-entrepreneurism, with focus on individual freedom and choice: appealing concepts for those experiencing precarity. This article challenges the rhetoric of Airbnb and investigates notions of home, authenticity and hospitality that are reconceptualized under a specific regime of digital biopolitics. Drawing on research conducted in four regional tourist towns in New Zealand this article analyses the biopolitical interpellations that impact hosts’ subjectivities as entities in motion and considers the ways that the rationalities of Airbnb’s algorithms modulate the embodied behaviours of its hosts.
Keywords: Airbnb; biopolitics; communications technology; digital technology; platform capitalism; tourism; 1606 Political Science; 1608 Sociology; 2002 Cultural Studies